Uso de 2-octil-cianoacrilato na reconstrução da cavidade anoftálmica de coelhos - Barbarini Ferraz, Lucieni Cristina [UNESP]; Schellini, Silvana Artioli [UNESP]; Wludarski, Sheila Lordelo; Padovani, Carlos Roberto [UNESP]; Müller, Sérgio [UNESP] (My University, 2007)
Purpose: To evaluate fixation by a bioadhesive of the external ocular muscles to the porous polyethylene spheres. Methods: An experimental study was performed using eight white rabbits that underwent right eye enucleation with placement of 12 mm spheres of porous polyethylene. The rectus muscles (superior and inferior) were attached to the implant with a bioadhesive (2-octyl-cyanoacrylate) applied to the inferior side of the external muscles. Ninety days after surgery the orbital content was removed and 4 animals were submitted to a tensile strength test of the muscle-sphere attachment and the other 4 to histological evaluation. Results: The tensile strength test showed that the rupture force was similar between the muscle and porous polyethylene sphere bond attachment and normal external ocular muscles. The histologic evaluation showed fibrous tissue reaction and muscle-sphere attachment with no deleterious effects to the tissues; a capsule formation around the spheres and new vessels inside the implant were also observed. Conclusion: 2-octyl-cyanoacrylate provides strength adhesion between muscles and spheres, with surgery time reduction and does not provoke deleterious effects on the orbital tissues. Thus, the bioadhesive might be a good choice for use in the anophthalmic cavity reconstruction.
2-octyl-cyanoacrylate in rabbit anophthalmic cavity reconstruction
Keywords: Adhesives/therapeutic use; Biomechanics; Cyanoacrylates; Histology; Oculomotor muscles/drug effects; Polyethylenes; Rabbits/surgery